Intracellular transglutaminase-catalyzed polymerization and assembly for bioimaging of hypoxic neuroblastoma cells. Issue 37 (30th August 2019) - Peng, Bo; Zhao, Xiao; Yang, Miao-Sen; Li, Li-Li
Abstract : An intracellular polymerization and assembly strategy was proposed for selectively bioimaging of hypoxic neuroblastoma cells, which was prospected for further tracing and locating brain tumors in vivo . Abstract : Hypoxia is an indicative feature of human neuroblastoma solid tumor. Bioimaging of hypoxic neuroblastoma cells will be beneficial for tracing and locating the tumor in vivo . In this work, we developed a hypoxic neuroblastoma cell imaging probe based on the mechanism of transglutaminase 2 (TG2)-catalyzed polymerization of fluorescence molecule-labeled peptide monomers and intracellular self-assembly of polymerized elastin-like polypeptides (ELPs) specifically for hypoxic neuroblastoma cells. The key influencing parameters, namely thermosensitivity, molecular weight, and upper critical solution temperature, for TG2-catalyzed polymerization into ELPs are discussed. More than 25 repeat units of ELPs were obtained by optimized TG2-catalyzed polymerization. The intracellular polymerization and assembly generated the assembly/aggregation-induced retention effect specifically in TG2-overexpressed cells ( e.g., HeLa) with retention efficiencies over 55% up to 24 h. Based on the up-regulation of TG2 expression under hypoxic conditions, our probe can selectively light hypoxic neuroblastoma cells rather than normoxic cells. Our strategy offers useful imaging probes to further study the mechanism of invasion and metastasis of hypoxic brain tumor in vivo with cell tracing and imaging functions.